Operationalizing One Health: strategic guidance for prevention and control of emerging and re-emerging vector-borne and zoonotic diseases in the Eastern Mediterranean Region - Kodama, Chiori; El Rifay, Amira S.; Badra, Rebecca; Abu Salbi, Rana; Abubakar, Abdinasir; Kayali, Ghazi (Frontiers in Tropical Diseases, 2023)
Operationalizing global One Health strategies at the field level to prevent and control vector-borne and zoonotic diseases (VBZDs) is of significant public health importance. Such strategies should be coordinated at the human-animal-ecosystems interface and applied at the national, regional, and global levels through the enforcement of effective policies. We aimed to develop a regional framework that can aid countries of the World Health Organization Eastern Mediterranean region to better prevent, detect, and respond to VBZDs events. This strategic guidance is a twelve-element framework drafted using various guidance documents and peer-reviewed scientific literatures, incorporating recommendations made through expert consultations. The framework elements were then integrated within a logical framework designed for practical implementation of One Health at regional and country level.